2015
DOI: 10.14814/phy2.12395
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic preconditioning accelerates muscle deoxygenation dynamics and enhances exercise endurance during the work-to-work test

Abstract: Ischemic preconditioning (IPC) improves maximal exercise performance. However, the potential mechanism(s) underlying the beneficial effects of IPC remain unknown. The dynamics of pulmonary oxygen uptake (VO2) and muscle deoxygenation during exercise is frequently used for assessing O2 supply and extraction. Thus, this study examined the effects of IPC on systemic and local O2 dynamics during the incremental step transitions from low- to moderate- and from moderate- to severe-intensity exercise. Fifteen healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
149
2
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 88 publications
(174 citation statements)
references
References 37 publications
(69 reference statements)
17
149
2
6
Order By: Relevance
“…Occlusion pressure for the group was between 160-170 mmHg, therefore 220 mmHg ensured the pressure was at least 50 mmHg above systolic blood pressure. This pressure is supported by similar IP literature (Bailey, Jones, et al 2012;de Groot et al 2010;Sharma et al 2015), however recent near infrared spectroscopy data indicates arterial pulses may be observed up to 300 mmHg (Kido et al 2015). Pilot data, collected using Doppler ultrasound, as well as published literature (Gibson et al 2013), identified 50 mmHg as an appropriate control pressure, as it provides a sensation of pressure, without impairing arterial flow.…”
Section: Ischaemic Preconditioningsupporting
confidence: 57%
“…Occlusion pressure for the group was between 160-170 mmHg, therefore 220 mmHg ensured the pressure was at least 50 mmHg above systolic blood pressure. This pressure is supported by similar IP literature (Bailey, Jones, et al 2012;de Groot et al 2010;Sharma et al 2015), however recent near infrared spectroscopy data indicates arterial pulses may be observed up to 300 mmHg (Kido et al 2015). Pilot data, collected using Doppler ultrasound, as well as published literature (Gibson et al 2013), identified 50 mmHg as an appropriate control pressure, as it provides a sensation of pressure, without impairing arterial flow.…”
Section: Ischaemic Preconditioningsupporting
confidence: 57%
“…IPC had no beneficial effects on the mean V ・ O2, V ・ E, and HR during a 5 km running time trial 22) , the submaximal V ・ O2 during maximal incremental leg cycling 13,14) , or during leg cycling at an exercise intensity of 90% V ・ O2peak at the gas exchange threshold 12) . However, IPC decreased LA at the submaximal running speed compared to SHAM 21) .…”
Section: Physiological Responses At Submaximal Work Loadmentioning
confidence: 88%
“…In fact, the maximal or peak oxygen uptake (V ・ O2max or V ・ O2peak) was not improved with IPC during maximal incremental exercise and during constant-load leg cycling at a work load of 130% peak power 10) or at 70% of the difference between the V ・ O2 at the gas exchange threshold and V ・ O2peak 12) . Likewise, the heart rate peak (HRpeak) was not increased with IPC during maximal incremental leg cycling 13) , during constant load leg cycling until exhaustion 11,12) , maximal HR during a 5 km running time trial 21) , and 100 m swimming 19) . Additionally, maximum pulmonary ventilation (V ・ Emax) during maximal incremental leg cycling 13,14) was not affected by IPC.…”
Section: Physiological Responses At Maximal Work Loadmentioning
confidence: 91%
See 2 more Smart Citations